Do fluoride toothpastes have similar preventive effect in permanent and primary teeth against erosive tooth wear?. Issue 2 (16th December 2018) - Assunção, Cristiane Meira; Schlueter, Nadine; Rodrigues, Jonas Almeida; Carvalho, Thiago Saads; Lussi, Adrian
Abstract : Background: Little is known about fluoride toothpastes effect on primary teeth submitted to erosive tooth wear. Objectives: To evaluate the preventive effect of different toothpastes on surface loss (SL) after severe erosion/abrasion model and to compare this effect between permanent (PT) and primary teeth (pt). Design: Enamel samples were randomly divided according toothpastes groups (n = 17). G1: placebo; G2: NaF; G3: AmF‐NaF‐SnCl2 anti‐erosion; G4: SnF2 ; and G5: NaF anti‐erosion for children. Samples were incubated in artificial saliva (1 hour), submitted to erosive challenge (3 minutes; 1% citric acid; pH3.6; at 25°C) and to toothbrush abrasion (2 minutes slurry immersion; 50 strokes; 200 g) during 30 cycles. Surface loss (μm; mean ± SD) was quantified by contactless profilometry. The effects of the two covariables "tooth" and "toothpaste" were analysed by non‐parametric ANOVA, variables with significant effects were tested by Wilcoxon tests. Results: pt showed significantly higher surface loss than PT in all groups ( P  < 0.001). The mean values of SL of each group were: G1 PT 18.18(±3.98), pt 25.65(±9.21); G2 PT 14.76(±2.82), pt 18.11(±3.92); G3 PT 12.62(±5.29), pt 15.61(±6.70); G4 PT 17.12(±2.24), pt 23.41(±7.9); G5 PT 13.24(±1.29), pt 18.28(±8.96). Conclusions: In permanent teeth, G3 showed the best preventive effect. In primary teeth, G1, G3, and G5 showed similar effect.